Exercises in Futility: Post-War Automobile-Trade Negotiations between Japan and the United States - Donald W. Katzner; Mikhail J. Nikomarvo (University of Massachusetts, Department of Economics, 2005)
This paper traces the history of the failed automobile-trade negotiations between Japan and the United States from the 1970s to the mid 1990s. It attributes the failure of those negotiations to a lack of understanding on both sides of not only what was motivating the other side, but also the unalterable cultural, social, and economic constraints under which the other side operated. JEL Categories: F13
Keywords: 330; automobile industry; US-Japanese trade negotiations